Development of an enzyme-linked immunosorbent assay for the detection of lolines in pastures. Issue 6 (2nd November 2017) - Briggs, Lyn; Tapper, Brian; Sprosen, Jan; Mace, Wade; Finch, Sarah
ABSTRACT: Polyclonal antibodies were produced in sheep for the development of a competitive enzyme-linked immunoassay for use in quantifying loline alkaloids in pasture samples. Lolines are aminopyrrolizidine secondary metabolites produced by fungal endophytes present in tall fescue and meadow fescue grasses, and confer increased resistance to a range of grass pests. Immunizing and plate coating antigens were prepared with derivatized loline dihydrochloride. Cross-reactivity studies indicated that the assay developed has broad specificity and antibody binding to loline analogues is affected by structural changes in the side chain of the loline molecule. Results obtained using the optimized immunoassay were compared with those determined by gas chromatography. The assay provides a sensitive and rapid analytical method that detects the loline analogues of interest and has been applied in pasture breeding programmes. The assay limit of quantitation for lolines in pasture is 3 µg/g in dried herbage.